BELIEVING IN NOT SEEING: TEACHING ATROCITY WITHOUT IMAGES. - PEARL, SHARRONA (Afterimage)
The article explores the abstract question of what happens to verbally painted portraits when assembled only in the mind's eye toward a greater understanding of the ethics of teaching atrocity through visual media. It discusses the role of pleasure in viewing practices through analysis of secondary works on atrocity images and the way they are used. It also examines various studies on disability through a close meditation on alternative looking practices in cases of extremity.